في أعداد ونشاط الفطريات والبكتريا في التربة Carbaryl 10D تأثير المبيد الحشري - حسن هذيليكاظم; غازي نغيمشرزاق; خلف الياسريمهدي (University of Thi-Qar Journal of Science, 2019)
A field and laboratories studies were carried out through 2008/2009 season to determine the effect of the insecticide Carbaryl 10D (which was spraying on palms to protect from Batrachedra amydrala) on the number and activity of fungi and bacteria in soil. The first study was conducted in seven palm orchards in Soq-Elshyookh / Thi-qar government by spraying 15 kgs from carbaryl 10D in two split application to six of these orchards. After 3 and 16 days, the number of fungi and bacteria in soil were determined and compared with their numbers before spraying . The insecticide didn’t affect fungi and bacteria numbers just in one state from six through the first three days and in the later days the numbers increased slightly. In the second and third study, the insecticide was mixed with soil in the levels ( 0 , 20 , 40 , 60 , 80 and 100 ) mg. kg -1 . A significant decrease was happened in the numbers of fungi and bacteria which reached 26 and 18.9 % respectively when using the insecticide in level 100 ) mg. kg -1 . Also there was a significant decrease in the microbial activity in the first days of incubation which was determined by measuring the quantity of CO2 released , the decreasing percentage was 14 and 21.9 % respectively when using the insecticide in level 100 ) mg. kg -1 .After the eighth day of incubation , the numbers of fungi and bacteria and their activity began to increase . أجريت تجارب حقلية ومختبرية خلال موسم 2009 /2008 لمعرفة تأثير المبيد الحشري فطريات وبكتريا التربة Carbaryl 10D في التجربة الأولى اختيرت ستة بساتين نخيل مزروعة بمحاصيل مختلفة في قضاء سوق الشيوخ في محافظة ذي قار ، رش المبيد المذكور على أشجار النخيل بما يعادل 51 كغم / ه ، أضيفت على دفعتين متساويتين بفارق 51 يوماً عن بعضهما ، كما تم اختيار بستان آخر )سابع( غير مزروع بأي محصول ولم يعامل بالمبيد . سجلت أعداد الفطريات والبكتريا قبل المكافحة وبعد 1 و 51 يوماً من ال رشة الأولى . بصورة عامة فان رش المبيد لم يؤثر معنوياً في أعداد الفطريات والبكتريا إلا في حالة واحدة من الحالات السبع وفي الثلاثة أيام الأولى فقط ، وفي الأيام اللاحقة كانت المحصلة زيادات طفيفة وغير معنوية في أعداد الفطريات والبكتريا وبنسبة 5001 و 101 % على التوالي . كما أجريت ) 500 ، 20 ، 10 ، 00 ، 80 ، تجربتين مختبريتين على بعض هذه الترب بإضافة المبيد خلطاً مع التربة بالت ا ركيز ) 0 ملغم كغم- 5. في التجربة الأولى لوحظ انخفاض معنوي في أعداد الفطريات والبكتريا بعد ثلاثة أيام من الحضن بنسبة 81 و 5202 % على التوالي عند استخدام المبيد بتركيز 500 ملغم كغم- 5 ، في حين ازدادت أعدادها بعد 51 يوماً من الحضن بنسبة 50 و 8502 % للفطريات والبكتريا على التوالي عند نفس التركيز أعلاه ، و في التجربة الثانية وجد أن المتحررة ( قد تأثر سلباً بوجود المبيد في الايام الاولى من الحضن ثم CO النشاط الميكروبي ) المقاس من خلال كمية 2 استقر النشاط وازداد بعد اليوم الثامن .